A Case Study of a Cut Slope Failure Influenced by Snowmelt and Rainfall. (2017) - Mori, Akira; Subramanian, Srikrishna Siva; Ishikawa, Tatsuya; Komatsu, Masahiro
Abstract: In cold regions, frequent incidents of soil slope failures occur due to snowmelt and rainfall. These failures are triggered by an increase in the degree of saturation of soil due to infiltration of water derived from rainfall and snowmelt. This study investigates a soil slope failure occurred on November 27, 2015 at a cut slope of an expressway in Hokkaido, Japan. The soil slope failure is investigated using a recommended stability assessment approach considering non-isothermal coupled seepage flow simulation followed by a limit equilibrium slope stability analysis. It is concluded that at the thawing period, the slope stability is affected by rainfall and snowmelt water infiltration and later in November the failure happened due to overflow of water from a drainage ditch.